Wacana Metta dalam Kakawin Ananda Bhuwana - Sangkaryang, Dewa; Cika, I Wayan; Jirnaya, I Ketut (Humanis, 2022)
Kakawin Ananda Bhuwana is an Old Javanese literary work that describes a character's journey in search of happiness (metta). The creativity and imaginative power of the author in compiling the story and giving the title to this literary work is a unique and special attraction. The theory used is the discourse theory proposed by Van Dijk. The analysis results of Kakawin Ananda Bhuwana's text show Kakawin Ananda Bhuwana as a constructor of metta discourse formed from a formal structure consisting of a macrostructure, a superstructure, and a microstructure.